Role of Teacher Professional Development on the Implementation of Inclusive Education Practices in Djibouti - Silam, Justus (American Journal of Education and Practice, 2024)
Purpose: The aim of the study was to assess the role of teacher professional development on the implementation of inclusive education practices in Djibouti. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that targeted and well-designed professional development programs equip educators with the necessary knowledge, skills, and strategies to create inclusive classroom environments. These programs often emphasize understanding diverse learning needs, adapting teaching methods accordingly, and fostering a supportive classroom culture that values equity and diversity. Teachers who participate in such programs are more likely to demonstrate increased confidence in addressing diverse student needs, utilizing inclusive teaching strategies, and collaborating effectively with colleagues, families, and support professionals. Moreover, studies highlight that sustained and ongoing professional development is essential for embedding inclusive practices into everyday teaching routines. Effective professional development initiatives often incorporate opportunities for reflection, feedback, and peer collaboration, allowing teachers to continuously refine their practices and respond flexibly to evolving student needs. By promoting a culture of continuous learning and improvement, these initiatives contribute to the overall effectiveness of inclusive education efforts within schools. Implications to Theory, Practice and Policy: Social learning theory, adult learning theory and communities of practice (CoP) theory may be used to anchor future studies on assessing the role of teacher professional development on the implementation of inclusive education practices in Djibouti. In the realm of practice, it is essential to tailor professional development programs to specific contextual factors such as school demographics, community needs, and student diversity. At the policy level, advocating for institutional support is crucial. Policies should provide sufficient resources, time, and support for implementing inclusive education practices.